8 An evaluation of end of life care for patients with Covid-19 receiving non-invasive pulmonary support. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Woods, Elizabeth; Snell, Kalyani; Zabrocki, Elizabeth; Reed, Elizabeth
Abstract : Background: Non-invasive pulmonary support (NIPS), (CPAP or NIV), is available to patients with Covid-19 and a ward based ceiling of treatment. Evidence demonstrate a 50% survival with NIPS in this cohort. We, and our respiratory colleagues, were interested to understand the experience of dying in this context. Method: This was a retrospective case note review. Aims and objectives include: To describe the symptoms experienced, medications required and reasons for withdrawal in patients dying of covid–19 following treatment with NIPS To evaluate care against the five priorities (NICE guideline (NG142)). Results: 18 patients were included for analysis. The majority were aged over 80 (67%). All patients experienced breathlessness when dying, and seventeen had agitation or delirium. Twelve patients (66%) required a regular benzodiazepine, either alone (22%) or in combination with an opioid (45%). Two patients (11%) were treated with only an opioid. The doses of opioids and midazolam were relatively small - most commonly 10 mg. 66% of patients received <3 as required doses of opioid or midazolam in the final 24 hours. The commonest reasons for withdrawal were the patient stopping tolerating treatment (56%), and treatment failure (28%). No patients died within three hours of withdrawal, with the majority dying six hours to two days later. In 17 cases (94%) it was recognised and documented that the patient was sick enough to die. This was communicated to the patient and/or their family in all 94%. All patients had a DNACPR and Treatment Escalation Plan. 94% of families were offered to visit their dying relative, this was taken up in 44% of cases. Conclusions: Good end of life care is achievable in the context of patients with Covid-19, receiving NIPs. Key learning includes: The need to regularly review symptoms and consider increasing background sc infusions more frequently than our usual practice of every 24 hrs.